Wave Energy Dynamics and Coastal Erosion: A Case Study on Narrow Neck Bay Auckland - Samaratunga, Chloe Tiara (Auckland University of Technology, 2022)
Coastal zones mark the boundary between land and sea and are actively evolving due the constant movement of waves. Sea waves are a dynamic feature of coastal zones that play a large role in the erosional processes that occur along the coast (Brocx & Semeniuk, 2009). Coastal views and accessibility to beaches is desired by many and has resulted in the suburban development of the coastal cliff edges at Narrow Neck, Auckland, New Zealand (Jongens, Gibb and Alloway, 2006). The properties along the cliff edge are very vulnerable to coastal hazards and therefore understanding the processes and factors of the coastal zone is important for the mitigation of potential hazards. This study aimed to track the waves impacting along the coast of Narrow Neck to determine wave dynamics such as direction, frequency, concentration and refraction, in order to understand wave energy transfer between sea waves and the coast. The link between sea waves and coastal geomorphology was also investigated to understand the wave dynamics observed and determine the influence wave action has on the coastal erosion occurring at Narrow Neck. The study was carried out by collecting both physical and digital field data. A physical geological survey was undertaken at the field location and digital, full motion video (FMV) footage of the coastal waves was captured using an unmanned aerial vehicle (UAV). The analysis was undertaken primarily using ArcGIS Pro software to process the data and produce the visual results. It was found that coastal waves and coastal erosion are strongly interconnected. The coastal wave dynamics of wave direction, concentration and frequency are influenced significantly by the geological landscape. The geological landscape was found to be heterogeneous along the coastline resulting in corresponding variation in sea wave dynamics. Differential erosion is occurring along the coast due to this variation, resulting in the development of erosional features which shape the coastline.